Photoelectric conversion based on peptide–porphyrin conjugates assembled hydrogel. (13th April 2021) - Li, Hongfang; Xing, Cuijuan; Huo, Weitao; Zhao, Jun; Hao, Yongchao; Hu, Zhangji
Abstract : Peptide–porphyrin conjugates facilitated porphyrin to participate in the assembly of hydrogel, improving the utilization of porphyrin and photoelectric conversion efficiency. Abstract : A porphyrin covalently modified peptide was synthesized and used as the basic building block to fabricate a hydrogel. The conjugate could facilitate porphyrin to participate in the assembly of the hydrogel, which resulted in enhanced hydrogel mechanical strength, improved porphyrin utilization and finally a promising photoelectric conversion system with a photocurrent density of 1.175 μA cm −2 .